5-year follow-up of spinal and sacroiliac MRI abnormalities in early axial spondyloarthritis - Madari, Queeny (2020)
Funding: g Devenir des Spondyloarthropathies Indifférenciées Récentes (DESIR) is financially supported by an unrestricted grant from Pfizer. AS is supported by a doctoral grant from 'Fundação para a Ciência e Tecnologia' (SFRH/ BD/108246/2015). The DESIR study is conducted as a Programme Hospitalier de Recherche Clinique with Assistance Publique Hopitaux de Paris as the sponsor. The DESIR study is also under the umbrella of the French Society of Rheumatology, which financially supports the cohort. An unrestricted grant from Pfizer as been allocated for the first 10 years.